Mathematical modeling and investigating the effect of the area of the horizontal stabilizer on the stability of a single-main-rotor helicopter in forward flight - Fatemeh Ghaderi; Farid Shahmiri (مجله مدل سازی در مهندسی, 2019)
This paper investigates the effect of the area of the horizontal stabilizer of a single-main-rotor helicopter on its dynamic responses, stability properties, and flight handling quality during forward flights. Taking linear aero-dynamical relations into account, and assuming a linear induced velocity for the rotor and two degrees of freedom of flapping and feathering for each blade, we have derived the six degrees of freedom nonlinear dynamical model of the helicopter consisting of a main rotor, tail rotor, horizontal stabilizer, vertical stabilizer, fuselage, and the thrust system. The paper covers our findings on the stability derivatives, the effect of the area of the horizontal stabilizer on the forward-flight stability of the helicopter. The results indicate that the trim flight conditions do not considerably change when the horizontal stabilizer area increases. Moreover, increasing the area of the horizontal stabilizer threefold has been found to improve the longitudinal stability of the helicopter—the poles of the open-loop system are transferred to the stability region. However, such stability is accompanied by a favorable overshoot and the settling time required for flight at level 1(ADS-33E); (overshoot less than 30% and the settling time less than 5 seconds.)